A STUDY OF SUBJECTIVE CAREER SUCCESS AND PERSONALITY TRAITS OF MIDDLE-LEVEL HOTEL MANAGERS IN THE HOSPITALITY INDUSTRY - Thi Hoai Nhung Duong (Tạp chí Khoa học Đại học Đà Lạt, 2025)
The present study investigates whether the Big Five personality traits can predict subjective career success. It uses socio-analytic and career congruence theories to predict individual outcomes, such as subjective career success. Data were obtained from 33 four- and five-star resorts and hotels operated by international and domestic chains in Vietnam. A total of 391 middle-level hotel managers were approached, using specific quotas for age, gender, education, and work experience. The final valid sample included 285 of the 297 respondents willing to participate. Confirmatory factor analysis and structural equation modeling were employed to investigate the hypothesized correlations between the constructs. Extraversion, conscientiousness, openness to experience, and agreeableness were found to positively predict, and neuroticism to negatively predict subjective career success. This result extends our understanding of the role of personality elements in determining career success. It also confirms the necessity of congruence between career success and personality. This result is crucial for those who provide career counseling and advice because, by knowing the connection between personality traits and subjective career success, they can better guide middle-level hotel managers in deciding on a relevant and appropriate career path.